Edu-Tourism Through Digital Literacy Based on Science and Technology in Community Empowerment Efforts to Improve the Economy in Banyuwangi Regency - Augustina Asih Rumanti; Amelia, Mia; Rizaldi, Artamevia Salsabila; Nurdinintya Athari Supratman (Metris: Jurnal Sains dan Teknologi, 2024)
This research aims to explore the role of science and technology-based edutourism in community empowerment efforts for economic improvement in Banyuwangi Regency, East Java. The subject matter studied includes the impact of the application of science and technology in edu-tourism programs on community economic improvement, strengthening the quality of education, and preserving local culture, improving the quality of human resources, utilizing technology in edu-tourism, and its impact on local economic development. The research method used was a literature study, as well as field research to collect relevant qualitative data. The data used includes data on the economy, education, tourism, and science and technology innovation in the education and tourism sectors. Based on the data analysis, this study highlights the importance of utilizing science and technology in the development of edu-tourism programs as an effort to improve the quality of the tourist experience, empower local communities, and strengthen the regional economy. The conclusion of this study shows that the implementation of science and technology-based edu-tourism has great potential to be one of the effective strategies in the effort to empower the community and improve the economy in Banyuwangi Regency. It is hoped that the results of this research can provide input for the government, educational institutions and tourism actors to develop edu-tourism programs in the form of sustainable digital modules and based on website technology to support economic and social development in Banyuwangi Regency.